Spatiotemporal variations and contributing factors of air pollutant concentrations in Malaysia during Movement Control Order due to pandemic COVID-19 - Ash’aari, Zulfa Hanan; Aris, Ahmad Zaharin; Ezani, Eliani; Ahmad Kamal, Nurfatin Izzati; Jaafar, Norlin; Jahaya, Jasrul Nizam; Abdul Manan, Shamsuri; Umar Saifuddin, Muhamad Firdaus (Taiwan Association for Aerosol Research, 2020)
The restriction of daily and economic-related activities due to COVID-19 pandemic via lockdown order has been reported to improve air quality. This study evaluated temporal and spatial variations of four major air pollutant concentrations across Malaysia before (March 4, 2020–March 17, 2020) and during the implementation of different phases of Movement Control Order (MCO) (March 18, 2020–May 12, 2020) from 65 official regulatory air quality stations. Results showed that restriction in daily and economic activities has remarkably reduced the air quality in all sub-urban, urban, and industrial settings with relatively small contributions from meteorological conditions. Overall, compared to before MCO, average concentrations of PM2.5, CO, and NO2 reduced by 23.1%, 21.74%, and 54.0%, respectively, while that of SO2 was constant. The highest reduction of PM2.5, CO, and NO2 were observed in stations located in urban setting, where 63% stations showed significant reduction (p < 0.05) for PM2.5 and CO, while all stations showed significant reduction in NO2 concentrations. It was also revealed that 70.5% stations recorded lower concentrations of PM2.5 during MCO compared to before MCO, despite that high numbers of local hotspots were observed simultaneously from NASA’s Moderate Resolution Imaging Spectroradiometer (MODIS). Spatial analysis showed that the northern part of Peninsular had the highest significant reduction of PM2.5, while the highest of NO2 and CO reduction were found in stations located in the central region. All pollutants exhibit similar diurnal trends when compared between pre- and during MCO although significant lower readings were observed during MCO. This study gives confidence to regulatory body; the enforcement of strict air pollution prevention and control policies could help in reducing pollution.